LAMELLARIID GASTROPODS COLLECTED BY JAPANESE ANTARCTIC RESEARCH EXPEDITIONS FROM NEAR SYOWA STATION AND BREID BAY, ANTARCTICA (Twelfth Symposium on Polar Biology) - ヌマナミ, ヒデキ; オクタニ, タカシ; NUMANAMI, Hideki; OKUTANI, Takashi (National Institute of Polar Research, 1991)
P(論文) Among the benthos materials collected from near Syowa Station, Breid Bay and Gunnerus Bank, Antarctica, four species of the lamellariid gastropods were found. The descriptions on a new species Marseniopsis syowaensis n. sp., and two known species, M. conica and M. mollis are given. A single specimen considered to be a new species from Breid Bay is described. Some ecological bearings of the lamellariid gastropods in the Antarctic are discussed. departmental bulletin paper